Analisis Pengukuran Ketepatan Antropometri Tinggi Badan Balita pada Pelatihan Kader Posyandu di Panduman Kecamatan Jelbuk - Rusdiarti Rusdiarti (Poltekkes Kemenkes Kendari, 2019)
The nutritional status of children under five is one indicator of the level of health in Indonesia. Nutritional status can help detect the risk of health problems early. Anthropometric measurements carried out by cadres at the posyandu include measurements of body length, weight and height measurements for infants and toddlers. The ability and accuracy of posyandu cadres in taking anthropometric measurements is very important, this is related to the wrong interpretation of nutritional status as well as decision making and planning for further treatment. The purpose of the study was to analyze the Effect of Posyandu Cadre Training on Anthropometric Measurement Skills. This study used a pre-experimental design research design. The population in this study were 35 cadres of Posyandu in Panduman village. The results of the study The value of the skills of the cadres of TB measurement training for children aged <2 years, pretest was 46.71 in the treatment group and 45.31 in the control group. The posttest in the treatment group was 82.24 while in the control group it was 50. And the value of training cadres in measuring TB for children aged> 2 years Pretest was 52.11 in the treatment group, and 49.33 in the control group. The posttest in the treatment group was 86.32 while in the control group it was 50.63. conclusion; The skills of a cadre in TB will determine the next intervention, errors in measuring TB affect the results of nutritional status data and management carried out. By practicing or simulating, it will be easier for cadres to remember what they have done by themselves and be seen firsthand.